Pathology of the liver in quails - Krupeshasharma S R (Centre of Excellence in Pathology, College of Veterinary and Animal Sciences, 1992)
A study was undertaken to assess the prevalence and nature of different types of lesions encountered in the liver of Japanese quails. To study the incidence of hepatic disorders in Japanese quails data were collected from the autopsy records maintained at the Centre of Excellence in pathology, College of Veterinary and Animal Sciences, Mannuthy for a period of six years from 1986 – 1991. The overall incidence of liver lesions was 34.09 per cent. The incidence was high in quails aged above 6 weeks and low in quail chicks. During the course of this investigation for the period 1990 to 1991, 575 livers with well defined gross lesions were examined for histopathological changes. The different type of lesions encountered were congestion (42.08 per cent), fatty change (30.26 per cent), subcapsular haemorrhage (0.34 per cent), abscesses (0.34 per cent), necrosis (6.78 per cent), Marek’s disease (18.43 per cent) and hepatitis (1.73 per cent). Congestion was the most common lesion observed. The incidence of congestion was 42.08 per cent. It was highest in quail chicks. In adults, in many cases, congestion was associated with other hepatic lesions whereas in quail chicks, congestion was observed as the only change in most of the cases. Out of 575 livers examined, hepatic abscesses were seen in two livers. In one liver gross abscesses were seen, where as in the other case abscesses were seen only in histologic sections. The incidence of fatty change was highest in adults. It was found that fatty change was the significant hepatic response to various toxic conditions in quails. Disintegration of the reticular fibres in case of extensive fatty change was demonstrated. Subcapsular haemorrhage was seen in two livers. Hepatitis was relatively uncommon in quails. It was recorded in 10 cases out of 575 livers examined. Marek’s disease lesions were noticed in 106 livers. Pathological features of Marek’s disease lesions in the liver of quails, were discussed in detail. S. typhimurium was isolated from three cases of hepatitis. Experimental infection was induced in quails with and without immunosuppression. It was observed that the hepatic lesions were more extensive and mortality was higher in immunosuppressed quails. The possible role of stress in enhancing the pathogenicity in field situations was clarified. The zoonotic importance of S. typhimurium infection was discussed. Hepatic toxicity of dietary monensin was studied. Hepatic steatosis was the consistent finding. It was clarified that liver is the target organ in monensin toxicity in quails. The practical importance of this toxicity was highlighted.